Chloride Improves Nitrate Utilization and NUE in Plants - Rosales, Miguel A.; Franco-Navarro, Juan D.; Peinado-Torrubia, Procopio; Díaz-Rueda, Pablo; Álvarez, Rosario; Colmenero-Flores, José M. (Frontiers in Plant Science, 2020)
Chloride (Cl‒) has traditionally been considered harmful to agriculture because of its toxic effects in saline soils and its antagonistic interaction with nitrate (NO3‒), which impairs NO3‒ nutrition. It has been largely believed that Cl‒ antagonizes NO3‒ uptake and accumulation in higher plants, reducing crop yield. However, we have recently uncovered new Cl‒ functions as a beneficial macronutrient, based on the improvement of plant growth, tissue water balance, plant water relations, photosynthetic performance, and water-use efficiency. The increased plant biomass indicates in turn that Cl‒ may also improve Nitrogen Use Efficiency (NUE). Considering that N availability is a bottleneck for the plant growth, the excessive NO3‒ fertilization frequently used in agriculture becomes a major environmental concern worldwide, causing excessive leaf NO3‒ accumulation in crops like vegetables and, consequently, a potential risk to human health. New farming practices aimed to enhance plant NUE by reducing NO3‒ fertilization should promote a healthier and more sustainable agriculture. Given the strong interaction between Cl‒ and NO3‒ homeostasis in plants, we have verified whether Cl‒ affects NO3‒ accumulation and NUE in plants. For the first time to our knowledge, we provided a direct demonstration showing that, contrary to impair NO3– nutrition, Cl– facilitates NO3– utilization and improves NUE in plants. This is largely due to Cl– improvement of the N-NO3– utilization efficiency (NUTE), having little or moderate effect on N-NO3– uptake efficiency (NUPE) when NO3– is used as the sole N source. Clear positive correlations between leaf Cl– content vs NUE/NUTE or plant growth have been established at both intra- and inter-species levels. Optimal NO3‒ vs Cl‒ ratios become a useful tool to increase crop yield and quality, to favouring the agriculture sustainability and reducing the negative ecological impact of NO3‒ in both the environment and in human health.